Long‐term safety and efficacy of AAV gene therapy in the canine model of glycogen storage disease type Ia. Issue 6 (25th May 2018) - Lee, Young Mok; Conlon, Thomas J.; Specht, Andrew; Coleman, Kirsten E.; Brown, Laurie M.; Estrella, Ana M.; Dambska, Monika; Dahlberg, Kathryn R.; Weinstein, David A.
Abstract: Background: Viral mediated gene therapy has progressed after overcoming early failures, and gene therapy has now been approved for several conditions in Europe and the USA. Glycogen storage disease (GSD) type Ia, caused by a deficiency of glucose‐6‐phosphatase‐α, has been viewed as an outstanding candidate for gene therapy. This follow‐up report describes the long‐term outcome for the naturally occurring GSD‐Ia dogs treated with rAAV‐GPE‐hG6PC‐mediated gene therapy. Methods: A total of seven dogs were treated with rAAV‐GPE‐hG6PC‐mediated gene therapy. The first four dogs were treated at birth, and three dogs were treated between 2 and 6 months of age to assess the efficacy and safety in animals with mature livers. Blood and urine samples, radiographic studies, histological evaluation, and biodistribution were assessed. Results: Gene therapy improved survival in the GSD‐Ia dogs. With treatment, the biochemical studies normalized for the duration of the study (up to 7 years). None of the rAAV‐GPE‐hG6PC‐treated dogs had focal hepatic lesions or renal abnormalities. Dogs treated at birth required a second dose of rAAV after 2–4 months; gene therapy after hepatic maturation resulted in improved efficacy after a single dose. Conclusion: rAAV‐GPE‐hG6PC treatment in GSD‐Ia dogs was found to be safe and efficacious. GSD‐Ia is an attractive target for human gene therapy since it is a monogenic disorder with limited tissue involvement. Blood glucose and lactate monitoring can be used to assess effectiveness and as a biomarker of success. GSD‐Ia can also serve as a model for other hepatic monogenic disorders.